Oxidative stress and metabolic biomarkers in patients with psoriasis: Oxidative stress in relation to psoriasis - Klisic, Aleksandra (Journal of Medical Biochemistry, 2023)
Background: Psoriasis is an autoinflammatory disease that affects not only skin, but multiple organs thus being associated with many comorbidities. Oxidative stress and inflammation play the major role in the pathogenesis of this disease. Studies that examined by-products of oxidative stress in psoriasis show discrepant results. Hence, we aimed to examine the oxidative stress, inflammation and metabolic markers and to explore their potential relationship with disease severity in patients with psoriasis.Methods: This case-control study comprised of 35 patients with psoriasis and 35 age, sex and body mass index-matched healthy controls. Metabolic and oxidative stress biomarkers [i.e., malondialdehyde (MDA), advanced oxidation protein products (AOPP), and catalase (CAT)] were measured. The principal component analysis (PCA) was employed to reduce the number of measured variables into smaller number of factors. Results: Higher AOPP levels (p20. Conclusion: Multimarker approach showed that metabolic and renal function related factor and oxidative stress-hepatic related factor were better predictors of psoriasis severity than each single examined biomarker.
Keywords: cytokines; inflammation; oxidative stress; psoriasis